Analysing culture methods of frozen human ovarian tissue to improve follicle survival. Issue 1 (March 2021) - Bjarkadottir, Briet D; Walker, Charlotte A; Fatum, Muhammad; Lane, Sheila; Williams, Suzannah A
Abstract : In vitro follicle growth is a potential fertility preservation method for patients for whom current methods are contraindicated. Currently, this method has only been successful using fresh ovarian tissue. Since many patients who may benefit from this treatment currently have cryopreserved ovarian tissue in storage, optimising in vitro follicle growth (IVG) for cryopreserved-thawed tissue is critical. This study sought to improve the first step of IVG by comparing different short-term culture systems for cryopreserved-thawed human ovarian tissue, in order to yield a higher number of healthy multilayer follicles. We compared two commonly used culture media (αMEM and McCoy's 5A), and three plate conditions (300 µL, 1 mL on a polycarbonate membrane and 1 mL in a gas-permeable plate) on the health and development of follicles after 6 days of culture. A total of 5797 follicles from three post-pubertal patients (aged 21.3 ± 2.3 years) were analysed across six different culture conditions and non-cultured control. All culture systems supported follicle development and there was no difference in developmental progression between the different conditions tested. Differences in follicle morphology were evident with follicles cultured in low volume conditions having significantly greater odds of being graded as morphologically normal compared to other conditions. Furthermore, culture in a low volume of αMEM resulted in the highest proportion of morphologically normal primary and multilayer follicles (23.8% compared to 6.3-19.9% depending on condition). We, therefore, recommend culturing cryopreserved human ovarian tissue in a low volume of αMEM to support follicle health and development. Lay summary: Ovaries contain a large number of follicles, each containing an immature egg and other important cells. Cancer treatments can lead to long-lasting negative side effects to the ovaries including the destruction of follicles, resulting in infertility. One strategy to preserve fertility is freezing of ovaries or ovarian tissue in girls and women undergoing cancer treatment. The long-term aim is to thaw and grow their ovarian tissue in the laboratory to obtain mature eggs, which can then be fertilised. In this study, we compared six different methods of growing previously frozen human ovarian tissue in order to best support follicle growth and health. We found that using the lowest amount of αMEM medium (a specific type of nutrient-rich growth solution) resulted in the highest proportion of healthy follicles. Improving the methods used to grow ovarian tissue, particularly frozen tissue, is important for future fertility preservation.